Comparison of Syphilis Rapid Diagnostic Test to Rapid Plasma Reagin, Treponema pallidum Haemagglutination Assay and Fluorescent Treponemal Antibody-Absorption for Syphilis and Yaws Diagnostics - Astuti Giantini; Dewi Wulandari; Siskawati Suparmin (The Indonesian Biomedical Journal, 2020)
BACKGROUND: Syphilis and yaws are the treponemal infections which have become serious public health problems, and both are serologically indistinguishable. Developed serological tests for syphilis may also be used to diagnose yaws. In remote area, test modality with minimal requirements were needed. This study investigated the diagnostic value of syphilis rapid diagnostic test (RDT) in diagnosing syphilis and yaws.METHODS: For syphilis diagnostic test, serum samples were obtained from patients of outpatient clinic in Dr. Cipto Mangunkusumo National Central General Hospital who were sent for rapid plasma reagin (RPR) and Treponema pallidum haemagglutination assay (TPHA) to clinical laboratory of the hospital. The serum samples were collected and stored at -80°C until the day of testing for syphilis RDT and fluorescent treponemal antibody-absorption (FTA-Abs). For yaws diagnostic test, serum samples were obtained as a part of surveillance study of yaws among children 1-15 years old in West Halmahera. Venous blood samples were used for syphilis RDT and the sera were separated and were sent to Dr. Cipto Mangunkusumo National Central General Hospital for RPR, TPHA, and FTA-Abs tests.RESULTS: For syphilis diagnostic test, among 156 samples, 39 samples were positive with syphilis RDT. The sensitivity of syphilis RDT was similar to RPR and TPHA (100.0%), the specificity was same as TPHA (77.5%), but lower than RPR (84.8%) when compared to FTA-Abs IgM. The sensitivity of syphilis RDT was 62.5% and the specificity was 96.0% when compare to FTA-Abs IgG. For yaws diagnostic test, among 176 samples, 13 samples were positive with syphilis RDT. By using FTA-Abs IgM as gold standard for diagnosing yaws, the RDT have similar sensitivity (50.0%) with RPR and TPHA and syphilis RDT have similar specificity to TPHA (93.1%). If compared to FTA-Abs IgG, the sensitivity of syphilis RDT was 40.0% and the specificity was 98.0%.CONCLUSION: Syphilis RDT gives similar results with TPHA in syphilis and yaws cases. It may be used as a first line screening test latent or untreated syphilis and yaws because of good sensitivity. For yaws diagnosis Syphilis RDT, RPR, and TPHA have low sensitivity, however all those tests have an excellent agreement.KEYWORDS: FTA-Abs, rapid diagnostic test, syphilis, yaws